Kinship Terms in Bantawa, Yakkha, Koyee and Lohorung: A Comparative Study - Rai, Tara Mani (Nepalese Linguistics, 2025)
This paper examines the kinship terminologies of four Kirati languages: Bantawa, Yakkha, Koyee, and Lohorung. Through a comparative analysis of both consanguineal (blood) and affinal (marital) relations, the study identifies patterns of cognancy, innovation, and typological variation. The findings reveal a strong shared core fundamental terms (e.g. papa 'father', mama 'mother') distinguishing relatives by age, gender, and lineage. Besides, there are significant lexical divergence among the Kirati languages, Bantawam Yakkha, Koyee and Lohorung in peripheral and affinal terms. However, Lohorung exhibits more innovative kinship terms in relation to other Kirati languages discussed in this paper. This study contributes to the understanding of the linguistic relatedness along with the social organization and cultural historicity of the Kirati people.